Corrupção dos países e componente anormal da Book-Tax Differences: uma análise mutlinível - Silva, Jéssica Rayse de Melo (2021)
This research propose to investigate whether perceived corruption, characteristic of the institutional environment of countries, is a determining factor for the abnormal component of the Book-Tax Differences (DA) of publicly-held companies. The thesis defended is that environments with a greater perception of corruption provide greater incentives for the opportunistic behavior of managers, which is reflected in DA. The evaluation of the proposed theoretical relationship was carried out through an adaptation of the Corruption Control metric, issued by Word Bank and, additionally as a sensitivity check, by the Perceived Corruption Index issued by Transparency International. 170,543 observations belonging to 99 countries were analyzed in the period from 2012 to 2018. Univariate and bivariate descriptive statistics techniques and multilevel modeling were used for inferential analyses. The results obtained through the application of three-level linear hierarchical models with repeated measures, provided evidence to support the inclusion of metrics related to countries' perceived corruption as an explanatory variable for DA. The research hypothesis, which addresses the positive association between DA and perceived corruption in countries, was not rejected for the total research sample and for the group of countries adopting IFRS. This suggests that for the IFRS Adopters group, the greater flexibility resulting from the internationalization of standards is opportunistically used by managers, who are possibly influenced by the low quality of the institutional environment. Thus, the results corroborate the assumption made by previous studies, that the low quality of company profits is associated with greater perceived corruption in countries. In addition to contributing to strengthening the theoretical framework that investigates the relationship between corruption in countries and the quality of accounting information, this research advances the literature in three other aspects: (i) by investigating the factors that, according to the literature, stimulate or mitigate the amount of BTD, the so-called determinants, from the perspective of segregation of components (normal component and abnormal component); (ii) by investigating variables of the companies' macro environment as determinants; and (iii) for using multilevel modeling to investigate the relationship between corruption in countries and DA. In practice, this study provides contributions to investors, investment analysts, regulators and regulators. The results demonstrate to investors and analysts that it is necessary to consider the institutional environment of countries for investment decisions, as the environmental context of countries can provide insights into possible levels of distortion in current performance arising from discretion over accounting and taxable income. For inspectors, the understanding of the determinants of DA can be used to more assertively guide the choice of companies that need inspection. In turn, standard setters can perceive that the analysis of the institutional context provides an incremental potential of information about the opportunistic behavior of companies, which can guide not only in the edition of accounting and tax rules, but also in identifying the need for revision and implementation of mechanisms to prevent and fight corruption.